2020
DOI: 10.3847/1538-4357/ab5fdb
|View full text |Cite|
|
Sign up to set email alerts
|

Modeling Dust and Starlight in Galaxies Observed by Spitzer and Herschel: The KINGFISH Sample

Abstract: Dust and starlight are modeled for the KINGFISH project galaxies. With data from 3.6µm to 500µm, models are strongly constrained. For each pixel in each galaxy we estimate (1) dust surface density; (2) q PAH , the dust mass fraction in PAHs; (3) distribution of starlight intensities heating the dust; (4) luminosity emitted by the dust; and (5) dust luminosity from regions with high starlight intensity. The models successfully reproduce both global and resolved spectral energy distributions. We provide well-res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
57
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 100 publications
(85 reference statements)
10
57
0
Order By: Relevance
“…(1) Far-IR line fluxes may be suppressed by optically thick continuum absorption (e.g., Scoville et al 2017a (Okada et al 2013;Salgado et al 2016), the Large Magellanic Cloud (Lebouteiller et al 2012;Chevance et al 2016), and local galaxies (Croxall et al 2012;Abdullah et al 2017;Bigiel et al 2020). (4) Metallicity may influence the strength of cooling lines and the PAHs (Cormier et al 2015;Smith et al 2017;Croxall et al 2017;Cormier et al 2019;Aniano et al 2020). However, direct effects on the PAH grains appear most pronounced at metallicities well below those seen in GOALS galaxies, which typically have Z/Z e ∼ 1-2 (Inami et al 2013;Díaz-Santos et al 2017).…”
Section: Alternative Explanations For Decreasing ò Pe With σ Irmentioning
confidence: 99%
“…(1) Far-IR line fluxes may be suppressed by optically thick continuum absorption (e.g., Scoville et al 2017a (Okada et al 2013;Salgado et al 2016), the Large Magellanic Cloud (Lebouteiller et al 2012;Chevance et al 2016), and local galaxies (Croxall et al 2012;Abdullah et al 2017;Bigiel et al 2020). (4) Metallicity may influence the strength of cooling lines and the PAHs (Cormier et al 2015;Smith et al 2017;Croxall et al 2017;Cormier et al 2019;Aniano et al 2020). However, direct effects on the PAH grains appear most pronounced at metallicities well below those seen in GOALS galaxies, which typically have Z/Z e ∼ 1-2 (Inami et al 2013;Díaz-Santos et al 2017).…”
Section: Alternative Explanations For Decreasing ò Pe With σ Irmentioning
confidence: 99%
“…18 The suffixes of model labels represent the total C abundance (per H nucleus) in ppm, e.g., MW3.1_60 means 60 ppm C/H in PAHs in this model (Weingartner & Draine 2001). Since the publication of the Draine & Li (2007) model, observations have suggested that the dust/gas ratio used in this model is systematically overestimated (Aniano et al 2020). Aniano et al (2020) found that a typical correction of ∼0.62 should be applied to dust mass derived from the Draine & Li (2007) model for their sample.…”
Section: Variations In Ssp Modelsmentioning
confidence: 99%
“…Since the publication of the Draine & Li (2007) model, observations have suggested that the dust/gas ratio used in this model is systematically overestimated (Aniano et al 2020). Aniano et al (2020) found that a typical correction of ∼0.62 should be applied to dust mass derived from the Draine & Li (2007) model for their sample. Thus, the conversion from carbon abundance (in ppm) to q PAH should be updated.…”
Section: Variations In Ssp Modelsmentioning
confidence: 99%
“…Although observational studies sometimes approximate galaxies' dust SEDs by one or two components in modifiedblackbody fitting, physical models based on assuming PDFs for the ISRF have been proposed and calculated by Dale et al (2001), Dale & Helou (2002), Li & Draine (2002), and (Draine & Li 2007, hereafter DL07). See also subsequent applications in Draine et al ( , 2014, Aniano et al (2012Aniano et al ( , 2020, Magdis et al (2012), Daddi et al (2015), Dale et al (2017), and Schreiber et al (2018).…”
Section: Introductionmentioning
confidence: 99%